A New Mobility Model for Ad Hoc Networks in Disaster Recovery Areas - Manaseer, Saher; Alawneh, Afnan (International Journal of Online and Biomedical Engineering (iJOE), 2017)
Over the last decade, many researchers have focused on Mobile Ad Hoc Networks as the main communication method in disaster recovery situations. In these researches, there has been marginal focus on the mobility patterns of nodes in disaster recovery scenarios. In this paper, a deeper analysis has been performed on some of the main mobility models used in testing new protocols and a new mobility model is proposed to incorporate some neglected factors concerned with disaster recovery situations.